Melanomacrophage centeres and diseases occurring in lesser-spotted catsharks, Scyliorhinus canicula (L.), from the southern Adriatic Sea : importance for monitoring - Gajić, Andrej (Array, 2020)
Melanomacrophages of fish are commonly explored as biomarkers of water pollution and are considered to be sensitive albeit non-specific health indicators in water ecosystems. Sharks as long living marine species are good sentinel species. This study presents morphometric data for splenic and hepatic melanomacrophages (MMC), and observed histopathology in ten lesser-spotted catsharks, Scyliorhinus canicula (L.), one of the most abundant shark species in the eastern Adriatic Sea. At necropsy, we collected random tissue samples from liver, brain, gallblader, pancreas, spleen, kidney, gills, entire digestive system, thyroid gland, rectal gland, entire urogenital (male samples) and genital system (female samples). Collected tissue samples were routinely processed and stained with hematoxylin-eosin, Periodic Acid-Schiff, and Masson Trichrome for microscopic examinations and morphometry. There was a minimal number of histopathological lesions in the examined sharks, but morphometric values reported herein were three folds higher than in previous studies in free-ranging sharks. Studies on larger numbers of sharks are needed to elucidate the biological significance of our finding in the context of population decline of the lesser-spotted catshark.